Ceria Entrapped Palladium Novel Composites for Hydrogen Oxidation Reaction in Alkaline Medium. Issue 5 (21st February 2020) - Ralbag, Noam; Davydova, Elena S.; Mann-Lahav, Meirav; Cong, Peixi; He, Jin; Beale, Andrew M.; Grader, Gideon S.; Avnir, David; Dekel, Dario R.
Abstract : A new heterogeneous catalyst for hydrogen oxidation reaction (HOR), metallic palladium within which nanoparticles of ceria are entrapped, CeO2 @Pd, is described. Its preparation is based on a new materials methodology of molecular doping of metals. The metallic matrix, which encages the nanoparticles, is prepared in foam architecture, to ensure easy molecular diffusion. Characterization of the structural properties of the CeO2 @Pd composite using SEM, STEM, TEM, XRD, EXAFS and nitrogen adsorption reveals its morphological architecture, which leads to improved catalytic activity. In-situ electrochemical and H2 temperature-programmed reduction (H2 -TPR) spectra provide direct experimental evidence of the weakening of Pd‒H bond in the CeO2 @Pd composites, relative to pure (undoped) Pd catalysts. Gas diffusion electrodes based on the entrapped CeO2 @Pd catalysts demonstrated one order of magnitude higher activity than pure Pd analog in the HOR reaction in an alkaline medium.